New indexing methods for different types of spatial data - Gu, Tu (Nanyang Technological University, 2024)
With the proliferation of GPS devices, spatial data is being generated at an unprecedented speed. Sometimes spatial data come with textual information and temporal information, forming spatio-textual data and trajectory data respectively. We are also seeing significant growths in the interest in the management and analysis tasks (e.g., query processing) on different types of spatial data, which increasingly rely on good indexes. In this thesis, we explore various methods to build indexes for spatial data, spatio-textual data and trajectory data, in order to facilitate efficient query processing.